Creating A Web-Based Patient Registration Application At Puskesmas Kampung Dalam - Anugerah Catur Wijanarko; Herry Surya Kasimo (JUDIMAS, 2021)
Puskesmas is a government agency that deals with public health services. Puskesmas is responsible for organizing health development at work. As Kampung Dalam Health Center serves many patients seeking treatment every day, the patient queue can become very crowded, which prompted the author to take an interest in creating her website-based software. I'm here. This study aims to design a website-based software as a vehicle for online public health services in the Kampong Dalam Community Health Center. The form of research in this community development is a case study by a research method based on the design research method. Various data collection techniques such as observations, interviews, and documentation are performed with the goal of identifying problems with the object and finding out how the website system is designed. In this study, researchers used the CodeIgniter framework by implementing functionality provided by the Bootstrap framework and MySQL as a database. Now, community development is creating website-based software to make it easier for the public to register for medical services online and for Puskesmas to easily manage patient data for treatment.